Study of growth kinetics of Fe3Se4 nanocrystallites and the influence of size and shape tunability on their magnetic properties - Ghalawat, Monika; Poddar, Pankaj (Journal of Physical Chemistry C, 2021)
Crystalline iron selenide (Fe3Se4) nanoparticles (NPs) present a useful model system for a fundamental understanding of magnetism apart from having potential applications in permanent-magnet-related technologies. Despite significant advancements in understanding of the nucleation and growth processes, control over size and shape tunability is nontrivial, especially for the transition metal chalcogenides (TMC). The Wulff theorem states that if a crystal can grow purely under thermodynamic control of parameters then it will adopt the shape determined by the surface-energy minimization, i.e., the surface energy minimization will drive the growth of each crystalline facet. However, the known or unknown, controllable or uncontrollable parameters of a typical reaction which makes kinetic growth more art than science, depending upon whether we understand them or not. There is hardly any study based on existing models and theories to explain the TMC morphology evolution. In this work, there is a conscious effort to know, understand, and control the individual role of various reaction pathways on the shape and size of the Fe3Se4 nanocrystals. A qualitative growth mechanism is proposed based on the diffusion and reaction processes. Furthermore, the influence of shape/size on the magnetic parameters such as coercivity (H-C), magnetization (M-60kOe), effective magnetic anisotropy constant (K-eff), energy product (BHmax), and average blocking temperature (T-B) is investigated for Fe3Se4 NPs. After diving deeper into the science of crystal growth, our insight provides valuable guidance on experimental conditions for the synthesis of Fe3Se4 NPs with tunable sizes/shapes which for the first time can be extended to most TMCs.